2012
DOI: 10.1002/art.33380
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing practices in a US cohort of rheumatoid arthritis patients before and after publication of the American College of Rheumatology treatment recommendations

Abstract: Purpose To examine prescribing of biologic and nonbiologic disease-modifying anti-rheumatic drugs (nbDMARDs) in Rheumatoid Arthritis (RA) before and after publication of the American College of Rheumatology (ACR) treatment recommendations. Methods We identified biologic naïve RA patients cared for by US rheumatologists participating in the CORRONA registry with visits prior to and/or at least 6 months after publication of the ACR recommendations (time periods: 2/02 - 6/08 vs. 12/08 - 12/09). The population w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 69 publications
(90 reference statements)
3
61
0
Order By: Relevance
“…In addition, in clinical practice, patients with RA in Japan are often prescribed lower doses of MTX (< 9 mg per week in average doses 14,15 , until recently) compared with patients in the United States (> 15 mg per week 16 ), which may theoretically affect the response to, and tolerability of, concomitant RA medication. Therefore, investigating the efficacy and safety of baricitinib in an Asian population is important before initiating phase III studies.…”
Section: Rheumatologymentioning
confidence: 99%
“…In addition, in clinical practice, patients with RA in Japan are often prescribed lower doses of MTX (< 9 mg per week in average doses 14,15 , until recently) compared with patients in the United States (> 15 mg per week 16 ), which may theoretically affect the response to, and tolerability of, concomitant RA medication. Therefore, investigating the efficacy and safety of baricitinib in an Asian population is important before initiating phase III studies.…”
Section: Rheumatologymentioning
confidence: 99%
“…A recent investigation observed that close to 50% of RA patients did not receive care consistent with the 2008 ACR guidelines. 22 Our study identifies some of the potential factors that may be contributing to this worrisome trend.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…Researchers have thus explored the relationship between corticosteroid and biologic DMARD use in clinical practice [6][7][8][9][10]. For example, it was found that corticosteroids are often used as RA treatment prior to initiating DMARDs despite recommendations that all patients should be managed with a DMARD [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many patients are not managed according to treatment guidelines, with significant delay in initiating DMARDs [7][8][9][10][11]. Researchers have thus explored the relationship between corticosteroid and biologic DMARD use in clinical practice [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%